Effect of La2O3 addition on mechanical properties and wear behaviour of NiTi alloy fabricated by direct metal deposition. (September 2020) - Lu, Bingwen; Cui, Xiufang; Jin, Guo; Dong, Meiling; Fang, Yongchao; Wen, Xin; Ma, Wenyou
Highlight: The addition of La2 O3 presented remarkable grain refinement of DMDed NiTi alloy. The strength of DMDed NiTi alloy was significantly promoted by La2 O3 addition. The promotion of wear resistance is ascribed to higher degree of superelasticity. Abstract: Additive manufacturing of NiTi alloys has received significant attention recently, but its insufficient strength and wear resistance need to be improved. In this work, NiTi alloys with and without La2 O3 addition were fabricated by direct metal deposition (DMD) technology. The influence of La2 O3 addition on the microstructure, mechanical properties and wear resistance of DMDed NiTi alloy was investigated. The results showed that the grain and the microstructure uniformity of the DMDed NiTi alloy were significantly refined and improved respectively after La2 O3 addition. Besides, the microhardness and tensile strength were remarkably promoted, which were mainly attributed to the synergistic action of the grain refinement strengthening of NiTi phase and second phase strengthening of NiTi2 or La2 O3 phases. Moreover, the addition of La2 O3 significantly improved the wear resistance of DMDed NiTi alloy due to the higher degree of superelasticity and finer hard phase.